Enhancing Meteor Observations with Photodiode Detectors - Adam Popowicz; Jerzy Fiołka; Jacek Chęciński; Krzysztof Bernacki (Applied Sciences)
This article introduces an innovative meteor detection system that integrates high-speed photodiode detectors with traditional camera-based systems. The system employs four photodiodes to record changes in sky brightness at 100 Hz, enabling meteor detection and the observation of their dynamics. This technology serves as a valuable complement to existing imaging techniques, offering a cost-effective solution for measuring meteor ablation at frequencies beyond the capabilities of camera-based systems. We showcase findings from the Perseid meteor shower, demonstrating the potential of our system. Moreover, our system addresses the current limitations in meteor radiometry, where many existing instruments either remain in developmental stages or have not been validated with a substantial number of confirmed meteor events. Our approach successfully addresses these limitations, demonstrating effectiveness across multiple meteor events simultaneously recorded on video.